PENGARUH GOOD CORPORATE GOVERNANCE, KONSERVATISME AKUNTANSI DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Sektor Properti Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Salma Maisaroh; Kurnia Rina Ariani (JURNAL LENTERA AKUNTANSI, 2024)
This study aims to analyze the effect of Good Corporate Governance, accounting conservatism, and company size on earnings management (empirical study of property sector companies listed on the Indonesia Stock Exchange 2018-2022). This research method is quantitative. The object of this research is the annual report and audit report of Real Estate and property companies listed on the Indonesia Stock Exchange (IDX) for 2018-2022. The sampling method of this research is purposive sampling, with techniques based on judgment sampling considerations. The data used in this study are secondary. The data collection method is the documentation method. The analytical tool used in this research is multiple regression analysis with the help of the IBM Statistical Package for Sciences (SPSS) program version 26. The result of this study is that Good Corporate Governance has no significant effect on earnings management. Accounting conservatism hurts earnings management. Company size does not affect earnings management.